People’s social value depends on their sexual orientation and gender identity - Lima, Kaline da Silva (2022)
The present study aimed to investigate discrimination against transsexuals. A experimental study was carried out that consisted in the presentation of a fictitious news about photos of a person that were leaked according to the victim’s gender assigned at birth (male vs. female), their sexual orientation and gender identity (heterosexual vs. Homossexual vs. transsexual), resulting in six experimental conditions. The measure of discrimination used was the allocation of the indemnification amount. The study included 300 cisgender heterosexual participants of both genders, randomly allocated in one of the six experimental conditions. The results enhanced the evidence that people tend to value their own group and discriminate against transsexual people. Variations were found regarding the target gender and the discriminator’s gender. The findings were discussed based on the Social Identity Theory and the threat to distinctiveness.